(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2020)
The stars and the particle colliders prove that all things are made up of the same thing. This same thing has been called Konke. This was discussed in the paper “The Algorithm of Information and the Origin of Basic Particles.” This paper will show that this konke must get into relationships to become basic mass, particles. It will show how we categorize particles by mass and the behavior of that mass in the same class of particles. Because we know everything is in a relationship and all relationships take energy to maintain, resulting in a loss of freedom giving that relationship structure, there must be another variable that provides the energy for konke to get into a variable. This other variable is called V2, or variable 2. This V2 would be considered the original force as it allows konke to get into relationships; it thus gives other forces the ability to exist. Theoretically, this V2 behaves in many ways to what has been termed gravity. A collider is proof enough for konke given the first law of thermodynamics; energy can neither be created nor destroyed.